Ethical dilemmas in college campus victim advocacy - Woods, Kathryn Scott, author; Bubar, Roe, advisor; Tungate, Sue, committee member; Opsal, Tara, committee member; Cespedes, Karina, committee member; McShane, Katie, committee member (Colorado State University. Libraries, 2016)
This dissertation examines ethical dilemmas in college campus victim advocacy. Dilemmas were identified by experts in the field of college campus victim advocacy. A Grounded Theory approach was used to identify categories of dilemmas, and interviews were conducted with experts in the field. Ultimately, dilemmas were identified that led to participants experiencing significant institutional trauma. These dilemmas related, not to working with individual survivors, but rather to working within broken systems and navigating complicated relationships with other professionals. Participants’ own and survivors’ identities were also explored, and ultimately also related back to systems and the “bad” professionals working within them. Based on these findings, implications for future research are discussed.